PENGARUH MATAKULIAH KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT MAHASISWA UNTUK BERWIRAUSAHA (STUDI KASUS PADA MAHASISWA STIE PELITA NUSANTARA SEMARANG) - Lies Indriyatni (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
This research aims on knowing the effect of giving Entrepreneurship courses in raising students’ interest to be entrepreneurs, by comparing between students’, who have already taken entrepreneurship course, interest and students’, who haven’t taken entrepreneurship course yet, interest using double regression test. We took 30 samples each from 2nd semester student, 4th semester student and 6th semester student. The result that we found is that there is effect of giving Entrepreneurship course in students’ interest to be entrepreneur, however it is low since each group’s result got Adjusted R2 less than 0.2. For 2nd semester student, even though they haven’t received Entrepreneurship course until they reach later year, they had ever received the subject when they were in high school. As for 4th semester student, they tend to like jobs which can give them regularly stable income guarantee (becoming employees). From this result, we can get information that the teaching method for Entrepreneurship course has to be accompanied by direct practice on the field so that the student can get clearer explanation about how to start a business (do entrepreneurship).